Historical and Multidisciplinary Perspectives on Hope - van den Heuvel, Steven C. (Springer Nature, 2020)
This open access volume makes an important contribution to the ongoing research on hope theory by combining insights from both its long history and its increasing multi-disciplinarity. In the first part, it recognizes the importance of the centuries-old reflection on hope by offering historical perspectives and tracing it back to ancient Greek philosophy. At the same time, it provides novel perspectives on often-overlooked historical theories and developments and challenges established views. The second part of the volume documents the state of the art of current research in hope across eight disciplines, which are philosophy, theology, psychology, economy, sociology, health studies, ecology, and development studies. Taken together, this volume provides an integrated view on hope as a multi-faced phenomenon. It contributes to the further understanding of hope as an essential human capacity, with the possibility of transforming our human societies.